Prevalence and burden of gastrointestinal parasites of Djallonke sheep in Ayeduase, Kumasi, Ghana - Owusu, Moses (Vet World, 2016)
AIM: This study was conducted to determine the prevalence and burden of gastrointestinal (GIT) parasites of Djallonke sheep in Ayeduase, Kumasi from January 2015 to July 2015. MATERIALS AND METHODS: The presence of nematodal eggs and coccidial oocysts in fecal samples were analyzed using the saturated sodium chloride floatation technique. Identification of eggs or oocysts was done on the basis of morphology and size of the eggs or oocysts. RESULTS: Out of 110 fecal samples of sheep examined, 108 were infected with GIT parasites, representing a prevalence rate of 98.2%. The total infection rate of GIT nematodes and coccidia oocysts were 94.5% and 51.8%, respectively. Strongyle nematode (94.5%) was the most prevalent GIT nematode detected, followed by strongyloides (27.3%). The average nematodal burden in g/feces was significantly higher (p<0.001) in young rams under 1 year (3482.0) than gimmers (1539.0), lamb (825.0), ewes (420.7), and rams over 1 year (313.3). Nematodal burden in gimmers was significantly higher (p<0.001) than that of lambs, ewes, and rams over 1 year. Nematodal counts of lambs, ewes, and rams did not differ significantly (p>0.05) from each other. The average coccidia oocysts count in g/feces was significantly higher (p<0.001) in lambs (2475.0) than rams under 1 year (286.0), gimmers (263.6), ewes (158.6), and rams over 1 year (150.0). There was no significant difference (p>0.05) in the coccidia oocysts count of rams under 1 year, gimmers, ewes, and rams over 1 year. From the studied animals, 40%, 6.36%, 48.18%, and 5.45% had heavy, moderate, light, and no infestation, respectively, with GIT nematodes. CONCLUSION: Djallonke sheep in Ayeduase, Kumasi, were infested with varying amounts of GIT parasites. The infestation of Djallonke sheep by GIT parasites also varies among different age groups and sexes.